TITLE - Seydou OUATTARA (Georeview, 2024)
In the era of containerization of goods, container terminals represent essential links in a port's logistics chain. They constitute a point of contact between the outside world and the port. They have been the subject of numerous scientific discussions because of their importance in port traffic. However, they focused on the management or operation of the terminal in general to the detriment of specific operations, particularly handling. The objective of this study is to understand the mechanisms ofmanagement of port handling operations within the TC11. The methods used to obtain the results are part of a qualitative approach. This involves documentary research, direct observation and semi-structured interviews using interview guides with TC1 managers. It appears that the management of the Vridi container terminal (TC1) makes it possible to coordinate three types of operations : operations linked to the loading and unloading of ships, storage and handling operations and finally operations of transfer or delivery of containers thanks to the road and rail connection. The temporal and geographical coordination of all these activities is a guarantee of the competitiveness of TC1